Relevance of Biogas in Rural Area: Women Perspectives - Khadka, Gopal (Patan Pragya, 2020)
Biogas is a form of clean cooking mechanism. As a proven and widely-used global source of energy, it is popular all over the world. To explore the women's views about the importance of biogas in rural settings of urban areas, this study is conducted as the title of relevance of biogas in rural areas: women perspectives. It is based on the theoretical assumption of cultural feminism. It employs exploratory research design and is based on both primary and secondary sources of data. The study revealed that there is high relevance of biogas in rural farm based society in Nepal. Through women perspectives, health and sanitation; easy and sustainable operation; time and resource saver; cheap and low maintenance are its major importance. Biogas plant helps to reduce the untiring busy schedule of women in household activities. It suggests that concerned authorities should make effective institutional frameworks to empower women in their homeland by optimum utilization of leisure time made possible by the use of biogas.